Effective Methods of TRIZ Technology in the Formation of Inventive Abilities of Primary School Pupils - Maftuna Ganiyeva (International Journal on Integrated Education, 2021)
The success of TRIZ originates from the fact that other common techniques are limited in their ability to solve internal problems by the actors' experience and knowledge. That is, TRIZ can stimulate and build problem-solving thinking and expertise. In contrast to other approaches that appear to be conditional and constrained. This article discusses the effective methods of TRIZ technology in shaping the inventive abilities of primary school students.